Polylactic acid vs. polyacrylamide hydrogel for treatment of facial lipoatrophy: a randomized controlled trial [Agence Nationale de Recherches sur le SIDA et les Hépatites Virales (ANRS) 132 SMILE]1. Issue 7 (24th February 2013) - Lafaurie, M; Dolivo, M; Girard, P‐M; May, T; Bouchaud, O; Carbonnel, E; Madelaine, I; Loze, B; Porcher, R; Molina, J‐M; ,
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to demonstrate the noninferiority of polyacrylamide hydrogel (PH) vs. polylactic acid (PLA) for the treatment of facial lipoatrophy in HIV‐infected adults. Methods A randomized, blinded, multicentre, noninferiority 96‐week study was carried out. Patients with facial lipoatrophy were randomly assigned to receive intradermal injections with PH or PLA, and were blinded to the filler. The primary efficacy endpoint was patient satisfaction at week 48 assessed using a visual analogue scale score (VAS). Secondary efficacy end‐points included cheek thickness and skin‐fold, lipoatrophy grading and quality of life. Safety was assessed by the reporting of adverse events. Results A total of 148 patients were included in the study; 93% were men, the median age was 47 years, the median CD4 count was 528 cells/μL, and the median duration of antiretroviral therapy was 12 years. Mean VAS increased from 2.8 at baseline to 7.1 and 7.5 in the PLA and PH arms, respectively, at week 48 (P = 0.0002 for noninferiority) and was sustained at week 96 (6.7 and 7.9 in the PLA and PH arms, respectively; P = 0.003 for noninferiority). Cheek thickness and skin‐fold increases and lipoatrophy improvement were similar in the two arms. Quality of life remained unchanged or improved depending on the questionnaire used. In injected patients, subcutaneous nodules emerged in 28 (41%) and 26 (37%) patients in the PLA and PH arms, respectively (P = 0.73). Four patients in the PH arm developed severe inflammatory nodules, a median of 17 months after the last injection. Conclusions PH and PLA have similar efficacies in the treatment of facial lipoatrophy, but PH may be associated with more delayed inflammatory nodules.